Long-term survival of a patient with recurrent gallbladder carcinoma, treated with chemotherapy, immunotherapy, and surgery: a case report - Makoto Kawamoto; Yoshiyuki Wada; Norihiro Koya; Yuko Takami; Hideki Saitsu; Naoki Ishizaki; Mineo Tabata; Hideya Onishi; Masafumi Nakamura; Takashi Morisaki (Surgical Case Reports)
Abstract Background Gallbladder cancer (GBC) is one of the refractory diseases. Multidisciplinary approach including immunotherapy for such cancers has received much attention in recent years. Case presentation A 59-year-old man underwent an extended cholecystectomy for GBC (pathological stage II, T2 N0 M0, [per UICC 7th edition]) that was incidentally found during cholelithiasis surgery, and was then treated with adjuvant gemcitabine (GEM). Three months later, when a recurrence-suspected lesion was detected in segment 5 (S5) of his liver, we started adoptive immunotherapies with cytokine-activated killer (CAK) cell infusions, combined with chemotherapy. After a year of adjuvant immunochemotherapy, the S5 lesion disappeared on imaging, but lesions suspected metastatic recurrence again appeared in S7 and S8 at 4 years and 6 months post-surgery, for which GEM and cisplatin (CDDP) were administered as second-line chemotherapy. Immunochemotherapy produced stable disease (per RECIST) for 9 months, when tumor growth was detected; open microwave coagulo-necrotic therapy (MCN) was performed for these lesions. Three years after MCN, a solitary liver metastasis was detected in S4. MCN was conducted again, and peritoneal dissemination was found intraoperatively. A month after the second MCN, the patient’s carcinoembryonic antigen (CEA) level had increased. Therefore, GEM and tegafur-gimeracil-oteracil potassium (TS-1) were administered as third-line chemotherapy. We also switched the adoptive immunotherapy for tumor-associated antigen-pulsed dendritic cell-activated killer (DAK) cell immunotherapy. After nine courses of GEM and TS-1 administration, CEA had decreased to a normal level. At the time of reporting, 9 years and 6 months have passed since the initial surgery, and 18 months have passed since the peritoneal metastasis was detected. GEM and CDDP are currently administered as fourth-line chemotherapy because of re-increased CEA. Although an undeniable metastasis was found in his para-aortic lymph node, this patient visits our clinic regularly for immunotherapy. Conclusion We here report a rare case of long-term survival of recurrent GBC well controlled by multidisciplinary therapy. Immunotherapy may be a promising modality among multidisciplinary methods for advanced cancer.